Building intercultural maturity: Informal and incidental learning among volunteers in adult ESL contexts - Beixi Li (Adult Education Research Conference, 2020)
This empirical paper describes the preliminary results of a mixed-methods study about the relationship between informal and incidental learning among volunteers in adult ESL and their intercultural maturity.
Keywords: Adult ESL; informal and incidental learning; intercultural maturity; Global Perspective Inventory